The discrete charm of the Washington Consensus - Jan Kregel (Levy Economics Institute of Bard College, 2008)
Over the last two centuries in Latin America a Washington Consensus development strategy based on integration in the global trading system has dominated both domestic demand management and industrialization from within. This paper assesses the performance of each from the point of view of the impact of external conditions, and the validity of its underlying theory. It concludes by noting that replacing the Consensus will require not only reform of the international financial architecture but also a return to the integrated policy framework represented in the Havana Charter.
Keywords: B31; O11; O14; O16; O23; 330; Development Finance; Latin American Development Policy; Ragnar Nurkse; Development Economics; Employer of Last Resort; Entwicklungsstrategie; Außenhandelsliberalisierung; Globalsteuerung; Industrialisierung; Internationales Währungssystem; Lateinamerika